Sistem Pendukung Keputusan Penentuan Penerima Bantuan Keluarga Miskin Menggunakan Metode Analytical Hierarchy Process - Technique For Order Of Preference By Similarity To Ideal Solution(AHP-TOPSIS) - Akbar Aditya Maulana; Nurul Hidayat; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Economic growth is one of the major factors in which a contry can be said to be growing. Various ways undertook by the the Indonesian government to improve economic growth in indonesia, on of which is to suppress poverty in the territory of indonesia. Indonesia region that has a considerable povery level in East Java province, district of Situbondo regency Distric Mlandingan. Many ways are done by the government Situbondo to cope with poverty, especially by providing funds intended for the poor. However, the provison of funds is less appropriate target because there are still critizens who are categorized as capable, who are considered capable should not deserve help. For that need a decision suport system, to assist the Situbondo government to provide recommendations for candidates for help. By using AHP-TOPSIS method that will be applieds to an androids based application with 6 criterian that serve as a reference to get accuracy. Then by the TOPSIS method used to search from the preference for rank. In this research, a test is done to know the value of accuracy in TOPSIS method, and the result of accuracy with a value raching 80% by using TOPSIS method.